KNOWLEDGE LEVEL OF BASIC LIFE SUPPORT AND DISASTER PREPAREDNESS AMONG STUDENTS OF POLTEKKES KEMENKES TASIKMALAYA - Nisrina, Ghina Yuniar; Sukawan, Ari; Asriyanti, Asriyanti; Meilany, Lilik; Agustina, Agustina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Indonesia is located in the Asia Pacific region which frequently experiences various natural disasters, so knowledge about Basic Life Support (BLS) and disaster preparedness is very important. This knowledge influences individual behavior when providing emergency assistance. The Tasikmalaya Ministry of Health Polytechnic has a vision as a Health And Disaster Emergency Center (HADE Center) so that it has an important role in providing education and training related to emergencies and disasters. Tasikmalaya Ministry of Health Polytechnic students as prospective health service providers are expected to have adequate knowledge in this field. This research aims to determine the level of BLS knowledge and disaster preparedness among Tasikmalaya Ministry of Health Polytechnic students. This research uses a descriptive quantitative method with univariate analysis. Data were obtained through questionnaires filled out by 276 students selected using quota sampling techniques. The results showed that most students had good knowledge (41.7%) about BLS and quite good (40.6%) about disaster preparedness, so there is a need to increase knowledge in this field.